2008
DOI: 10.1128/aac.00506-08
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Activity of an Anti-Idiotypic Antibody-Derived Killer Peptide against Influenza A Virus Experimental Infection

Abstract: The in vitro and in vivo activities of a killer decapeptide (KP) against influenza A virus is described, and the mechanisms of action are suggested. KP represents the functional internal image of a yeast killer toxin that proved to exert antimicrobial and anti-human immunodeficiency virus type 1 (HIV-1) activities. Treatment with KP demonstrated a significant inhibitory activity on the replication of two strains of influenza A virus in different cell lines, as evaluated by hemagglutination, hemadsorption, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Previous works have demonstrated an antiviral activity for KP against other enveloped viruses, such as HIV, by internalization of the chemokine receptor type 5 (CCR5) in susceptible cells, and human and avian influenza viruses, by reduction of viral protein synthesis, in particular M1 and HA [25, 26]. In both cases, a direct KP interaction with viral envelope has been excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works have demonstrated an antiviral activity for KP against other enveloped viruses, such as HIV, by internalization of the chemokine receptor type 5 (CCR5) in susceptible cells, and human and avian influenza viruses, by reduction of viral protein synthesis, in particular M1 and HA [25, 26]. In both cases, a direct KP interaction with viral envelope has been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already demonstrated a wide-spectrum antimicrobial activity by KP and some of the other peptides [21, 23, 32]. Yet, the antiviral activity of such peptides has not been investigated yet, with the exception of KP, which has been shown to inhibit HIV as well as human and avian influenza viruses [25, 26]. The results of the present work expand our knowledge on KP, showing that it drastically reduces HSV-1 viral yield, at both 50 μg/mL (99%) and 100 μg/mL (99.99%) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, each lung was removed, weighed, and homogenized in minimal essential medium (MEM), and the viral titer was determined by the TCID 50 assay with MDCK cells. The number of wells showing a positive cytopathic effect was scored, and the titer (TCID 50 ) per milligram of lung tissue was calculated by standard procedures (28)(29)(30). All experimental procedures were approved by the Institutional Animal Care and Use Committee (IACUC) of Shantou University.…”
Section: Methodsmentioning
confidence: 99%
“…The mice were weighed daily for 21 days. Three mice per group were euthanized at day 6, when the virus titers in the lungs reached the maximum (28), and the viral titers in their lungs were analyzed. Briefly, each lung was removed, weighed, and homogenized in minimal essential medium (MEM), and the viral titer was determined by the TCID 50 assay with MDCK cells.…”
Section: Methodsmentioning
confidence: 99%